Corporate governance and performance of Government-Linked Companies (GLCS): GLC Transformation program effects / Mohd Afiq Azero, Nor'azam Mastuki and Rosiatimah Mohd Isa - Azero, Mohd Afiq; Mastuki, Nor 'Azam; Mohd Isa, Rosiatimah (2013)
The objective of this study is to examine the relationships of corporate governance mechanisms towards firm performance. The corporate mechanism under the study includes board characteristics (board size, board independent, multiple directorships and senior government officer) and board meeting frequency. Performance is measured using ROA, ROE, and EPS. This study uses data from the annual reports of 23 final samples of Government-Linked companies for the year 2004 to 2009. The regression results show that only board meeting frequency is significant and has negative relationship with performance.